Oil dependence is transport running out of affordable fuel?. (Round table (Transport Research Centre) ;, 2008)
Oil consumption is increasingly concentrated in transport and relatively limited fluctuations in transport demand can have increasingly significant effects on oil prices. This Round Table assesses the policy instruments available to address oil security and climate change and examines their interaction with measures to manage congestion and mitigate local air pollution. A number of incompatibilities and trade-offs are identified underlining the importance of integrated policy making. The report includes an examination of the factors that drive oil prices in the short and long term and a discussion of the outlook for oil supply.--Publisher's description.